THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT CENTURY SUPERMARKET TOMOHON - Gerungai, Gabriela G. V.; Saerang, David P. E.; Gunawan, Emilia M. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Leaders are expected to use a leadership style, communication skills, and their knowledge of interpersonal and team dynamics to create an appropriate quality of work life for their employee in the workplace. A leadership style is a combination of a leader’s attitude, expertise, character, and values that is exhibited in the leader’s behavior. Employee performance is an important factor that contributes to improve the outcomes, behavior and traits of the employees. It helps to improve the productivity of the organization. Employee performance includes executing defined duties, meeting deadlines, employee competency, and effectiveness and efficiency in doing work. The aim of this study is to know the influence of leadership style on employee’s performance at Century Supermarket Tomohon. This research used simple linear regression analysis with sample of 30 employees. The result shows leadership style has a significant influence on employee’s performance at Century Supermarket Tomohon. It have a good influence on employees performance, which makes them able to work effectively and efficiently, able to complete the assigned task, and understand the tasks assigned by the company. Central Supermarket Tomohon should always treat their employee’s the same as today. It’s improved the employee’s performance which is important for the company performance.  Keywords: leadership style, employee performance